The complete encyclopedia of African American history - Bracks, Lean'tin L.; Smith, Jessie Carney, 1930-; Giovanni, Nikki; Wynn, Linda T. (2014)
"The Complete Encyclopedia of African American history. This comprehensive resource explores the past, the progress, and the present of African Americans in four volumes, each building, complementing, and expanding on the previous volume."--Back cover
[v. 4]. Civil rights feats and facts / editors, Jessie Carney Smith, Linda T. Wynn. Arts and entertainment. Movements ; Artists ; Entertainers ; filmmakers ; Films ; Music ; Music entrepreneur ; Singers ; Literature ; Writers -- Civil rights. Cities and towns ; Freedom celebrations ; Protests ; Race consciousness ; Speeches -- Education. Colleges and universities ; Integration of colleges of universities ; Curriculum ; Educators ; Educators ; School desegregation ; Protest Training School -- Journalism. Journalists ; Magazines ; News services ; Newspapers -- Law and government. Attorneys ; Civil Rights Commission ; Civil rights laws and cases ; Executive order ; Federal Commission ; Federal officials-- and intervention ; The military ; Prisons ; Resolutions -- Organizations. Groups ; Leaders -- Political activists. Abolitionists ; Civil rights activists ; Lynching victim ; Protest letter -- Religion. Churches ; Leaders ; Religious education -- Sports. Automobile racing ; Baseball ; Basketball ; Bowling ; Boxing ; Cycling ; Football ; Golf ; Horse racing ; Olympics ; Tennis ; Sports writers
Includes bibliographical references and indexes
Keywords: African Americans -- Encyclopedias; African Americans -- History -- Encyclopedias; African Americans -- Social life and customs -- Encyclopedias; African Americans -- Intellectual life -- Encyclopedias; African Americans -- Biography -- Encyclopedias; African Americans -- Civil rights -- History; Encyclopedias; History; Encyclopedias